The Preliminary Concrete Delay Duration Influence on its Properties at Thermal Processing by Hot Air - Kugaevska, Ð¢Ð°Ñ‚Ñ–Ð°na; Sopov, Viktor; Shulgin, Volodymyr (International Journal of Engineering and Technology, 2018)
Reducing energy consumption in the manufacture of concrete products of factory production is always an urgent task. The use of heated air for creating soft modes of heat treatment of concrete products is proposed. The influence of soft heat treatment modes on the dynamics of the concrete samples strength at an early age has been established. The expediency of using soft heat treatment modes with the obligatory use of hardening accelerators is shown. With this approach, the heat treatment of concrete samples with heated air contributes to increasing the concrete compression strength in the early term of hardening: at the age of 1 day 1.94 ... 2.12 times; at the age of 3 days 1,25 ... 1,41 times.Â